Development and pilot testing of a Decision Aid (DA) for women with early-stage breast cancer considering contralateral prophylactic mastectomy. (August 2018) - ,; Rankin, Nicole; Musiello, Toni; Boyle, Fran; Zdenkowski, Nicholas; Skandarajah, Anita; Saunders, Christobel; Sundaresan, Puma; De Abreu Lourenco, Richard; Ager, B.; Jansen, J.; Porter, D.; et al.
Abstract: Objective: Describe the development, acceptability and feasibility of a Decision Aid (DA) for women with early-stage breast cancer (BC) at average contralateral breast cancer (CBC) risk considering contralateral prophylactic mastectomy (CPM). Methods: The DA was developed using the International Patient Decision Aid Standards (IPDAS) and the Ottawa Decision Support Framework. It provides evidence-based information about CPM in a booklet format combining text, graphs and images of surgical options. Twenty-three women with a history of early-stage breast cancer were interviewed in person or over the phone using a 'think aloud approach'. Framework analysis was used to code and analyse data. Results: Twenty-three women participated in the study. Mean age of participants was 58.6 years and time since diagnosis ranged from 14 months to 21 years. Five women had CPM and eighteen had not. Women strongly endorsed the DA. Many felt validated by a section on appearance and found information on average risk of recurrence and metastases helpful, however, noted the importance of discussing personal risk with their surgeon. Many requested more information on surgery details (time taken, recovery) and costs of the different options. Conclusion: The DA was acceptable to women, including the format, content and proposed implementation strategies. Practical and financial issues are important to women in considering treatment options. Practice implications: Women appreciate information about CPM at diagnosis and emphasised the importance of discussing potential downsides of the procedure in addition to benefits. The DA was considered acceptable to facilitate such discussions. Highlights: Women strongly endorse a decision aid on contralateral prophylactic surgery (CPM). Women are happy to receive this decision aid when considering surgical options. Women considering CPM want practical surgery details (time taken, costs of options). Women emphasised discussion with their surgeon would complement the decision aid.